Centenary Subjects : Race, Reason, and Rupture in the Americas - McDaniel, Shawn, 1979- (Book collections on Project MUSE., 2021)
"The equivocal contours of arielismo-one of the most influential anti-imperialist ideologies, spiritual movements, cultural models, and utopian pedagogies for Latin American youth in an epoch of rampant US interventionism"--